Combined exercise training and dietary interventions versus independent effect of exercise on ectopic fat in individuals with overweight and obesity: a systematic review, meta‐analysis, and meta-regression - Fatemeh Kazeminasab; Motahareh Mohebinejad; Mohammad Hossein Mahboobi; Maedeh Nojoumi; Saba Belyani; Reza Bagheri; Fred Dutheil (Journal of the International Society of Sports Nutrition, 2025)
Aim While it is well established that reducing ectopic fat can help prevent insulin resistance in individuals with overweight or obesity, it remains unclear whether diet alone, exercise alone, or their combination is most effective in reducing specific ectopic fat depots. Therefore, the objective of this study was to investigate the effects of diet-only, and combined diet-plus-exercise interventions versus exercise only on ectopic fat reduction, and weight loss in adults with overweight or obesity.Methods Web of Science, PubMed, and Scopus were searched for original articles, published until 1 March 2024 (no limitation on publication dates) that included diet only/or exercise and diet versus exercise alone on body weight, and ectopic fat in adults with overweight or obesity. Weighted mean differences (WMD) for body weight, liver fat, standardized mean differences (SMD) for visceral fat area (VFA), and intramuscular triglyceride (IMTG), and 95% confidence intervals (95% CI) were determined using random-effects models. Studies using noninvasive imaging techniques such as Computerized Tomography (CT), Magnetic Resonance Imaging (MRI), and hydrogen-based Magnetic Resonance Spectroscopy (H-MRs) for ectopic fat were included in this meta-analysis.Results A total of 17 studies, including 732 participants aged 24.27 to 70.5 years (309 participants with metabolic diseases, and 423 without metabolic diseases) and 38 intervention groups, met the inclusion criteria. The combined intervention of exercise and diet significantly reduced body weight compared to exercise alone [WMD = -2.85 kg, p = 0.001], with significant reductions observed in both adults with and without metabolic disease, and for interventions lasting more than 12 weeks. However, the combined intervention did not significantly reduce liver fat, VFA, or IMTG compared to exercise alone. Diet-only interventions significantly reduced body weight compared to exercise alone [WMD = -2.57 kg, p = 0.010], but did not significantly affect liver fat, VFA, or IMTG. Meta-regression indicated that weight loss was a significant moderator of the effect of combined interventions on VFA (coefficient: −0.15; p = 0.030), but not for other outcomes. Also, based on subgroup analysis by intervention duration, both exercise and calorie restriction interventions in long-term (more than 12 weeks) have been successful in decreasing VFA in adults with overweight/or obesity.Conclusion Combined exercise and dietary interventions are more effective than exercise alone in reducing body weight. While VFA was reduced following long-term interventions of exercise in combination with caloric restriction, our analyses showed no change in liver fat, or IMTG. Additional investigation is required to delve into the processes behind these findings and to pinpoint treatments that efficiently focus on reducing ectopic fat.